2014
DOI: 10.1002/2013wr014448
|View full text |Cite
|
Sign up to set email alerts
|

Heat flux modifications related to climate‐induced warming of large European lakes

Abstract: Within the last decades, the water temperature of several European lakes has risen. It is assumed that these temperature increases are due to a reconfiguration of the heat‐balance components. This study explores the dominant modifications of heat exchange with the atmosphere and their temporal evolutions. The objective is to identify the primary changes in heat fluxes and the sequence of events of the reconfiguration for the period 1984–2011. For this purpose, a model was applied to Lake Constance to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 26 publications
10
97
1
Order By: Relevance
“…Solar brightening [39,48] and decreases in cloud cover [49] lead to increased solar radiation reaching the lake surface. Schmid and Köster [39] found that 60% of LSWT in a central European lake was attributable to increasing air temperature, while the remaining 40% was attributable to increased solar radiation due to air quality improvements.…”
Section: Near-surface Warmingmentioning
confidence: 99%
“…Solar brightening [39,48] and decreases in cloud cover [49] lead to increased solar radiation reaching the lake surface. Schmid and Köster [39] found that 60% of LSWT in a central European lake was attributable to increasing air temperature, while the remaining 40% was attributable to increased solar radiation due to air quality improvements.…”
Section: Near-surface Warmingmentioning
confidence: 99%
“…The variable climate, such as the present changes, has effects on the lake heat balance [Wahl and Peeters, 2014]. The water surface temperature increased by 0.046 C yr 21 in the past decades [Fink et al, 2014] and the inflow temperatures of the Rhine River increased by 0.028 C yr…”
Section: Study Sitementioning
confidence: 99%
“…In addition to expected heat use, there is overwhelming evidence supporting temperature increases in surface waters due to climate change [Adrian et al, 2009;Arvola et al, 2010;Fink et al, 2014;IPCC, 2013]. Observed increasing water temperature is strongly correlated to the signal of increasing air temperatures [Livingstone, 2003;Straile et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that lake-specific characteristics will determine the response to climate change (for clarity and brevity, we refer to anthropogenic climate change simply as "climate change" or "climate" from now on). Local factors which affect climate warming of lakes include, among others, morphology (Toffolon et al, 2014), irradiance absorption (Kirillin, 2010;Williamson et al, 2015), local weather conditions (Zhong et al, 2016), stratification , atmospheric brightening (Fink et al, 2014a) and ice cover (Austin and Colman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of climate impact typically do not address these sorts of subtleties in lake dynamics due to a lack of data or difficulties in predicting future temperature and discharge conditions (Fenocchi et al, 2017). Several studies of large lakes suggest that major tributaries play only a minor role in climate-induced warming and deep-water oxygen renewal (Fink et al, 2014a;Schwefel et al, 2016). Mediumand smaller-scale lakes are, however, more abundant than large lakes (Verpoorter et al, 2014) and exhibit a greater degree of sensitivity to point sources of anthropogenic thermal input which can affect temperature and stratification (Kirillin et al, 2013;Råman Vinnå et al, 2017).…”
Section: Introductionmentioning
confidence: 99%